2017
DOI: 10.1186/s12284-017-0161-6
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping of Yield and Yield-related Traits Under Reproductive Stage Drought Stress in Rice (Oryza sativa L.)

Abstract: BackgroundThe identification and introgression of major-effect QTLs for grain yield under drought are some of the best and well-proven approaches for improving the drought tolerance of rice varieties. In the present study, we characterized Malaysian rice germplasm for yield and yield-related traits and identified significant trait marker associations by structured association mapping.ResultsThe drought screening was successful in screening germplasm with a yield reduction of up to 60% and heritability for grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 86 publications
4
66
0
Order By: Relevance
“…A minimum of two to a maximum of 14 alleles were detected among the accessions per marker, with an average of 4.7 alleles. This range is higher compared to 1-11 reported earlier 52 and comparable with that of a recent study involving rice accessions from Malaysia 53 . The PIC varied from 0.0392 to 0.8443, with an average of 0.4034.…”
Section: Genetic Diversitysupporting
confidence: 65%
“…A minimum of two to a maximum of 14 alleles were detected among the accessions per marker, with an average of 4.7 alleles. This range is higher compared to 1-11 reported earlier 52 and comparable with that of a recent study involving rice accessions from Malaysia 53 . The PIC varied from 0.0392 to 0.8443, with an average of 0.4034.…”
Section: Genetic Diversitysupporting
confidence: 65%
“…Low spikelet fertility observed under drought stress was responsible for the drastic reduction in grain yield and harvest index. The yield reduction of >50% under drought stress was reported in earlier studies [16][17][18]. A wide variation in yield, spikelet fertility, and harvest index suggested that the US rice germplasm collection includes both drought-tolerant and susceptible genotypes.…”
Section: Discussionmentioning
confidence: 64%
“…The MLM model integrates structure and kinship matrix (Q+K) which supposedly corrects the false-positive error to tune of 62.5%. Hence, MLM model has been popularly used in several cases for marker-traits association [12,19,44,46,72, 8185].…”
Section: Discussionmentioning
confidence: 99%
“…It utilizes natural variation [12], hence supposed to have great potential to evaluate and characterize a wide range of alleles. Several researchers have been reported the utility of association analysis in the identification of QTLs for different traits in rice, viz., Grain yield [13], grain yield under water deficit [14], deep root mass and the number of deep roots [15], grain quality traits [16], agronomic traits [17, 18], grain yield under reproductive drought stress [19], panicle architecture and spikelet’s/ panicle [20], plant height and grain yield [21].…”
Section: Introductionmentioning
confidence: 99%